Evaluasi Parameter Mutu Ekstrak Air Daun Tahongai (Kleinhovia hospita Linn) - kuncoro, Hadi; Nur Sopiati, Mutia; Rashif Rijai, Hifdzur; Agustina, Risna (Brawijaya University, 2022)
Tahongai (Kleinhovia hospita Linn) is a medicinal plant that has various properties. This study aims to determine standardization parameters the tahongai aqueous extract. The research method was carried out by macroscopic and microscopic observations on Tahongai powder, then extracted by infusion method. The aqueous extract was then subjected to organoleptic determination, identification of secondary metabolites, determination of water soluble content and determination of water content, heavy metal contamination determination, and microbial contamination test. The result for determination of standardization parameter were: yield of the infusion was 10.38961%. Organoleptic test showed solid form, medium characteristic odor, black color and bitter taste. Identification of secondary metabolites showed a group of secondary metabolites of saponins and triterpenoids. Determination of the water soluble extract content 11.648% and the water content 10.328%. Heavy metal contamination Hg, Cd, Cr, Ni, Pb and As respectively were <0.0001; <0.0001; 0.9167; 49.2815; <0.0001 and 44.1774 mg/Kg. Then on microbial contamination, the result was 8.8 x 103 colonies/g. Based on PERKABPOM No. 12 of 2014, the water extract of tahongai meets the minimum quality requirements for heavy metal content and microbial contamination.